IMPLEMENTASI PLAN-DO-CHECK-ACT (PDCA) BERBASIS KEY PERFORMANCE INDICATORS (KPI): STUDI KASUS DI SMP-SMA INTEGRAL AR-ROHMAH DAU MALANG - Poppy Rachman (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
This research is to analyze the process of development of quality management by using the cycled approach of PDCA (Plan-Do-Check-Act) based on KPI (Key Performance Indicators). This research was conducted at SMP-SMA Integral Ar-Rohmah